Lead poisoning due to gunshot bullet in contact with cerebrospinal fluid: case report - Madureira, Paulo Roberto de; Capitani, Eduardo Mello De; Vieira, Ronan José; Sakuma, Alice Momoyo; Toledo, Adriana Safioti; Mello, Suely Moreira (São Paulo Medical Journal, 2009)
CONTEXT: Lead poisoning due to retained gunshot bullets is a well-known clinical problem that is fairly frequently described in the literature. The risk factors for this occurrence relate mainly to whether the lead bullet is in contact with the joint fluid or cerebrospinal fluid (CSF). The treatment for these cases entails chelation therapy while symptoms are shown and definitive surgical removal of the bullet as a potential source of lead. The aim of this paper is to describe a clinical case of lead poisoning due to a retained gunshot bullet in contact with CSF. CASE REPORT: A 42-year-old male was hit by gunshot bullets during a holdup, and one of them was retained in the spinal cord. Six years later, he developed intense low back pain and underwent laminectomy. Nine years later, he then underwent arthrodesis on L5-S1, but he developed intense abdominal pain after the surgical procedure. For five years, he was treated with calcium versenate in five-day cycles, with a good response. The chelation therapy cycles showed great efficacy during symptomatic periods, thus reducing the symptoms and signs of poisoning and promoting great amounts of lead excretion, thereby reducing the total lead burden responsible for the symptoms. Fortunately, over the last four years, the symptoms have improved and the urine levels of aminolevulinic acid (ALA) have declined, to reach complete normalization. This shows that a healing process is probably taking place on the spinal wound, thereby isolating the bullet fragments from CSF contact.